Efficacy and Safety of a Novel Bioabsorbable Polymer-Coated, Everolimus-Eluting Coronary Stent. (April 2015) - Kereiakes, Dean J.; Meredith, Ian T.; Windecker, Stephan; Jobe, R. Lee; Mehta, Shamir R.; Sarembock, Ian J.; Feldman, Robert L.; Stein, Bernardo; Dubois, Christophe; Grady, Timothy; Saito, Shigeru; Kimura, Takeshi; et al.
<x xml:space="preserve">Abstract</x> Background— Drug eluting stents with durable polymers may be associated with hypersensitivity, delayed healing, and incomplete endothelialization, which may contribute to late/very late stent thrombosis and the need for prolonged dual antiplatelet therapy. Bioabsorbable polymers may facilitate stent healing, thus enhancing clinical safety. The SYNERGY stent is a thin-strut, platinum chromium metal alloy platform with an ultrathin bioabsorbable Poly(D, L-lactide-co-glycolide) abluminal everolimus-eluting polymer. We performed a multicenter, randomized controlled trial for regulatory approval to determine noninferiority of the SYNERGY stent to the durable polymer PROMUS Element Plus everolimus-eluting stent. Methods and Results— Patients (n=1684) scheduled to undergo percutaneous coronary intervention for non–ST-segment–elevation acute coronary syndrome or stable coronary artery disease were randomized to receive either the SYNERGY stent or the PROMUS Element Plus stent. The primary end point of 12-month target lesion failure was observed in 6.7% of SYNERGY and 6.5% PROMUS Element Plus treated subjects by intention-to-treat (P=0.83 for difference; P=0.0005 for noninferiority), and 6.4% in both the groups by per-protocol analysis (P=0.0003 for noninferiority). Clinically indicated revascularization of the target lesion or definite/probable stent thrombosis were observed in 2.6% versus 1.7% (P=0.21) and 0.4% versus 0.6% (P=0.50) of SYNERGY versus PROMUS Element Plus–treated subjects, respectively. Conclusions— In this randomized trial, the SYNERGY bioabsorbable polymer everolimus-eluting stent was noninferior to the PROMUS Element Plus everolimus-eluting stent with respect to 1-year target lesion failure. These data support the relative safety and efficacy of SYNERGY in a broad range of patients undergoing percutaneous coronary intervention. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01665053.